Mantenimiento, puesta en marcha y análisis de datos de funcionamiento del Banco Motor Diesel BT50 (2020)
The proposal to start up the Mazda BT50 Diesel engine bank begins from the need to take advantage of the resources of the Antonio Nariño University. The Motor Bank is taken over to be back into operation after 4 years of inactivity. Preventive and corrective maintenance is carried out, replacing supplies and damaged elements and restoring the engine to optimal operation. A verification of all the elements of the motor for a correct operation and to avoid failures during its use. In addition to this, an adaptation of the work environment in the faculty mechanics workshop was required to make it safe for students and all those who wish to use the engine, this includes the adaptation of an exhaust gas extractor and a suitable space for the correct use of the bank. Diagnostic tests were carried out on essential components of the engine using tools that the faculty possesses such as a multimeter, an oscilloscope, and an automotive scanner. To help students, guides were made so that they can practice with the elements that the University has, the versatility of the practical guides will allow their use in various subjects. To take control of its use and follow-up on the operations carried out, documentation is included for its maintenance and control. This was complemented with a simulation of the components of the Diesel engines to compare their behavior with the real one. Hoping that the bank will be very useful for the investigations of the people who use it.